Sentinel surveillance for travellers' diarrhoea in primary care - Sarvotham Tinnu S; Evans Meirion R; Northey Gemma; Thomas Daniel R; Howard Tony J (BMC Infectious Diseases, 2007)
Abstract Background Travellers' diarrhoea is the most common health problem among international travellers and much of the burden falls on general practitioners. We assessed whether sentinel surveillance based in primary care could be used to monitor changes in the epidemiology of travellers' diarrhoea. Methods A sentinel surveillance scheme of 30 volunteer general practices distributed throughout Wales provides weekly reports of consultations for eight infectious diseases to the national Communicable Disease Surveillance Centre. Travellers' diarrhoea was introduced as a new reportable infection in July 2002. Results Between 1 July 2002 and 31 March 2005 there were 90 reports of travellers' diarrhoea. The mean annual consultation rate was 15.2 per 100,000 population (95% confidence interval: 12.2–18.7), with the highest rates in summer, in people aged 15–24 years, and in travellers to Southern Europe. A higher proportion of travellers than expected had visited destinations outside Europe and North America when compared to the proportion of all United Kingdom travellers visiting these destinations (38% vs. 11%; Chi2 = 53.3, p < 0.0001). Conclusion Sentinel surveillance has the potential to monitor secular trends in travellers' diarrhoea and to help characterise population groups or travel destinations associated with higher risk.